PREVENTING RELIGIOUS PERSECUTION AGAINST AHMADIYAH - Afnan Anshori (Jurnal Theologia, 2012)
As a global phenomenon, religious persecution might occur within all religions as well as nations. In  Indonesia, this phenomenon occurs within Islam. One of the most controversial cases regarding religious persecution is the discrimination experienced by Ahmadiyah. Here, they could not perform religious activeties freely as they are prohibited to do so. In addition, their properties as well as their religious and educational facilities have been destroyed. To resolve this case, there are at least, two approaches that can be used, which include judicial and non-judicial strategies. This research suggests the use of non-judicial strategies, which aim at eradicating religious persecution experienced by Ahmadis by raising people’s consciousness about religious tolerance and human rights. This includes intra-religious dialogue and multicultural and human rights education. In terms of dialogue, this research suggests the use of intra-religious dialogue within Islam, especially between Ahmadiyah and orthodox Muslims.